(untitled) (Journal of the College of Basic Education, 2026)
Educational methods have evolved along with the development of life in today’s societies, which necessitated the pursuit of changing the individual’s life to confront this development through experience and imitation in learning based on the results of this behavior and the extent of tangible effects in daily life. Thus, the goal of the current research is to construct a form for evaluating the parts and steps of students’ productions in the Department of Art Education in the subject of Arabic Calligraphy and Ornamentation. The first chapter included the research problem. The researcher attempted to answer how to construct a model for evaluating the artistic productions of students in the Department of Art Education, the importance of the research, the limits of the research, and defining the terms included in the research title. The second chapter included a section on evaluation, Arabic calligraphy and ornamentation, and then indicators of the theoretical framework. The third chapter contained the research procedures and the research community consisting of the productions of students in the Department of Art Education, and how to select the sample, as well as constructing the tool, its validity and reliability, and the statistical methods used in the current research The study reached several results, including that the evaluation grades for artistic productions at this level are acceptable to this extent, and that a student in the Department of Art Education is studying the Principles of Arabic Calligraphy and Ornamentation in the second stage. In addition, the researcher considers this assessment to be good, given that the students are beginners in this field and are not professional calligraphers and ornamenters. The most important conclusion is that it is possible to teach calligraphic and ornamental skills given the availability of a successful method and the provision of appropriate conditions, in addition to recommendations, suggestions, and a list of sources.The appendices included the names of experts, the final form for analyzing artistic productions, and pictures of paintings.